PENGARUH KANDUNGAN CRISTALINE INDEKS SELULOSA PADA SERAT KENAF - Salim Salim; Waris Wibowo (Majalah Ilmiah Bahari Jogja, 2017)
This research is aimed at getting to know the influence of as much as 99% level of alkali treatment (NaOH) or 60 gram of each in one liter aqua and soaked during three hours, heated with the temperature of 140o Celsius during 10 hours. This research is also intended to know the combination of 99% level of Alkali treatment (NaOH) or 60 gram of each in one liter aqua and soaked during three hours continued with the heating with temperature around 140o Celsius during ten hours toward the content of crystalline index (Cl) which correlates with Kenaf fiber strength as composit material of nature fiber. The result of the research shows that the highest content of crystalline index is possessed on Alkali treatment which is combined with the heating as much as 79,908% followed by Alkali treatment as much as 68,389% extended by heating treatment as much as 62,707%. The research also shows that the lowest content of crystalline index is the untreated fiber as much as 62,045%.